Impact on Variation in Genome Content of Wild Cymbopogon flexuosus (Nees ex Steud) Collected from Different Ecological Locations of Karnataka, India - Jagadeeshan, Vidya; Muniraju, Suchetha; KJ, Thara Saraswathi (Asian Journal of Biological and Life Sciences)
The present work explores the variation in genome content of wild Cymbopogon flexuosus from different locations in Karnataka. Collected plant samples showed genotypic and phenotypic variations. The samples of wild Cymbopogon flexuosus (E1 and E2) were collected from Bannerghatta hills, Bangalore and Charmadi Ghat, Dakshina Kannada district, respectively. The locations for plant collection were selected based on ecological differences such as altitude, temperature, precipitation and soil type. The soil analysis revealed variation in macronutrient and micronutrient content and composition. The studies on E1 and E2 showed significant differences concerning morphological characteristics such as plant height, leaf length, inflorescence colour and essential oil content. Flow cytometry studies showed differences in genome size between E1 (2718 Mbp) and E2 (2211Mbp), even though their ploidy status was similar. Due to environmental variations in these ecotypes, the plants could be further explored for crop improvement as they continue to evolve in the wild and develop special traits like pest resistance and drought tolerance.
Keywords: Essential oil; Genome content; Morphology; Ploidy status; Wild Cymbopogon flexuosus